IMPROVING STUDENTS' SCIENCE ACHIEVEMENT THROUGH THE IMPLEMENTATION OF PROJECT-BASED LEARNING - Wiraprakasa, I Ketut Gede Teguh (Journal of Psychology and Instruction, 2019)
Science learning is said to be more meaningful if students are involved in various project activities and their achievements during the learning process are often associated with their critical thinking skills. In this regard, this paper aims to find out how science learning outcomes in terms of critical thinking skills are enhanced through the application of project-based learning. The research design used was a post-test only control group design with a total sample of 128 Grade V students of Cluster I in Buleleng District. Data collected through tests and analyzed using ANAVA two paths to determine the effect of learning models on science learning outcomes in terms of critical thinking skills and the interaction between learning models with critical thinking skills. The results of the analysis show that 1) there are significant differences in science learning outcomes between students who take project-based learning and students who use conventional learning models; 2) there is a significant interaction between the application of project-based learning models and critical thinking skills on the learning outcomes of Natural Sciences; 3) students with high critical thinking skills tend to show more significant results on improving learning outcomes. However, the results of this study are limited to the measurement of critical thinking skills so that further research is needed by paying attention to other mediator variables.